The Jesus handbook - Schröter, Jens 1961-; Jacobi, Christine 1979-; Brawley, Robert L. 1939- (Chicago Wm. B. Eerdmans Publishing Co., 2022)
Intro -- Title Page -- Copyright -- Contents -- Foreword by Dale C. Allison Jr. -- Preface -- Translator's Preface -- List of Abbreviations -- A. Introduction -- I. About This Handbook -- II. The Earthly Jesus and the Christ of Confession: Contours of the Jesus Quest -- III. The Jesus Quest in the Age of Critical Historiography -- IV. The "Remembered Jesus"-on the Relevance of a Paradigm of Current Jesus Research -- V. Historical Material as a Foundation for the Reconstruction of the Deeds and Fate of Jesus -- VI. Early Impacts of Jesus -- VII. Literature for Basic Orientation -- B. History of Historical-Critical Research on Jesus -- I. Introduction -- II. The Earthly Jesus in the Piety and Theology of Antiquity, the Middle Ages, and the Reformation -- 1. Antiquity -- 2. The Middle Ages/Humanism -- 3. Reformation -- III. The Eighteenth Century as the Context for the Origin of Critical Theology -- 1. Critical Philosophy -- 2. Critical Philosophy of Religion -- 3. Critical Theology -- 4. Historical-Critical Exegesis -- IV. Critical Historiography of the Late Eighteenth and Nineteenth Centuries and Its Implications for Jesus Research -- 1. Critical Historiography of the Late Eighteenth and Nineteenth Centuries: Periodization and Characterization -- 2. Effects on Jesus Research -- V. The Concept of Myth in Historical Jesus Research and the Rise of the Two-Document Hypothesis -- 1. Strauss and the Concept of Myth -- 2. Reactions against Strauss and the Development of Markan Priority -- 3. Historical Jesus Studies, 1830-1870 -- 4. The Emergence of the Liberal Lives of Jesus -- 5. The Nineteenth Century in Retrospect -- VI. The "Kingdom of God" as an Eschatological Concept: Johannes Weiss and Albert Schweitzer -- 1. Introduction -- 2. Weiss's and Schweitzer's Kingdom -- 3. Weiss's and Schweitzer's Interpretation -- 4. Some Closing Thoughts.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books